2012
DOI: 10.1155/2012/193570
|View full text |Cite
|
Sign up to set email alerts
|

Use of i-scan Endoscopic Image Enhancement Technology in Clinical Practice to Assist in Diagnostic and Therapeutic Endoscopy: A Case Series and Review of the Literature

Abstract: Background. i-scan is a software-driven technology that allows modifications of sharpness, hue, and contrast to enhance mucosal imaging. It uses postimage acquisition software with real-time mapping technology embedded in the endoscopic processor. Aims. To review applications of i-scan technology in clinical endoscopic practice. Methods. This is a case series of 20 consecutive patients who underwent endoscopic procedures where i-scan image enhancement algorithms were applied. The main outcome measures were to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In our study, the validity of I-scan as a diagnostic test was 90.2% accuracy (95% CI were from 76.87% to 97.28%), 91.9% sensitivity, 75% specificity, 97.1% PPV and 50% NPV compared to WLE, which achieved 68.2% accuracy (95% CI were from 51.91% to 81.92%), 67.6% sensitivity, 75% specificity, 96% PPV and 20% NPV. Our result was in agreement with Hancock and et al who studied the uses of I-scan and concluded that it helped in the diagnosis of neoplastic changes as Barrett's esophagus, gastric lymphoma, duodenal adenoma and lymphoma [16].…”
Section: Table (1)supporting
confidence: 93%
“…In our study, the validity of I-scan as a diagnostic test was 90.2% accuracy (95% CI were from 76.87% to 97.28%), 91.9% sensitivity, 75% specificity, 97.1% PPV and 50% NPV compared to WLE, which achieved 68.2% accuracy (95% CI were from 51.91% to 81.92%), 67.6% sensitivity, 75% specificity, 96% PPV and 20% NPV. Our result was in agreement with Hancock and et al who studied the uses of I-scan and concluded that it helped in the diagnosis of neoplastic changes as Barrett's esophagus, gastric lymphoma, duodenal adenoma and lymphoma [16].…”
Section: Table (1)supporting
confidence: 93%
“…The proposed framework consists of image preprocessing and the SegNet architecture for polyp image segmentation, as shown in Figure 1. In the image preprocessing step, 1000 polyp images in the Kvasir-SEG dataset are applied to the histogram equalization 29 to improve the image contrast. After that, all enhanced images can be resized to provide 360 × 480 pixels.…”
Section: The Proposed Frameworkmentioning
confidence: 99%
“…I-SCAN improves polyp characterization and visualizes the architectural subtleties in the mucosa [30][31][32][33] (Figures 3, 4). …”
Section: I-scanmentioning
confidence: 99%